The Prevalence of Glaucoma and Its Related Factors in Rural Residents: A Cross-Sectional Study in Jiangxi, China - Xiaojun Zhou; Qin Zhu; Jinglin Yi; Jiajunni Li; Qi Li; Jie Kuang; Yuanan Lu; Rui Zhou; Jiayan Chen (Journal of Ophthalmology)
Background. This study aims to investigate the prevalence of glaucoma and its related factors among residents aged 40 and over in Jiangxi Province, China, and provide a scientific basis for the prevention and control of glaucoma. Methods. The cluster sampling method was used to randomly select six townships. Similarly, eight villages were randomly selected from each sample township. A total of 5385 rural residents from 48 villages were collected for a questionnaire survey. A logistic regression model was used to explore the personal behavioral factors related to glaucoma. Results. Among the 5385 participants, the prevalence rate of glaucoma was 1.4%. The logistic regression model found that alcohol consumption, vegetable consumption, physical exercise, daily reading time, and frequent reading environment were related to glaucoma. Conclusion. To prevent the occurrence of glaucoma, it is important for rural residents to reduce the frequency of alcohol consumption, increase the frequency of vegetable consumption and physical exercise, control the length of daily reading, and read in a moderately lit environment.